Rumours of Wars and Disasters: José Emilio Pacheco in Vancouver - Koss, Zane (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2025)
This essay reads poems by José Emilio Pacheco, a prominent twentieth-century Mexican poet, about his time in Vancouver, Canada, where he worked as a visiting professor at the University of British Columbia in 1969 and 1970. These poems operate through a poetic speaker caught in a state of “in-between-ness” – at once exiled, nostalgic, and unmoored yet actively engaged in denouncing state-sponsored terrorism, war, and environmental destruction from a position defined by spatial, temporal, and jurisdictional ambiguity and instability. Reading Pacheco’s “Canadian” poems, in turn, offers a new perspective on his more canonical poetry.